Cell therapy in Parkinson's disease and factors affecting the success - Jorquiera-Johnson, Tamara (2015)
Objective: To determine the factors that influence improvement of patients with Parkinson's disease treated with autologous adult stem cells from bone marrow by intra-arterial infusion. Material and Methods: An observational, analytical and retrospective study. We evaluated 58 patients with Parkinson's disease (PD) who received cell therapy at the Brazzini Institute of Interventional Radiology, between July 2006 and March 2010. The improvement was determined by comparing the UPDRS values before the procedure and the best values of patient monitoring. SPSS version 15.0 was used for analysis of relationship between improvement and intrinsic factors of the patient and his disease. P <0.05 to determine statistical significance. Results: 62% of patients achieved a good improvement in UPDRS values (more than 50% improvement). No significant differences (p> 0.05) in the results of improvement were found by gender. Significant differences (p <0.05) in the improvement according to age groups. Patients with more improvement were in the group of 50-59 years and those with little improvement were in the group of 70-79 years. Intrinsic factors such as severe dyskinesia, hypertension, diabetes mellitus, cancer in remission, family history of PD and month of follow-up did not influence the result of improvement (p> 0.05). Conclusion: Factors influencing the improvement in patients treated with cell therapy for PD are patient's age at disease onset and age at treatment. We recommend using these factors to choose patients who receive this therapy.